Twitter Discourse on the Pre-Presidential Election Campaign in Nigeria - Kadijat, Kadiri Kehinde; Ayotunde, Kehinde Adetola; Haroon-Sulyman, Shakirat Oluwatosin (Universitas Semarang, 2020)
Citizens political participation and engagement on various social media handles have made it necessary for scholars to investigate and understand the potentials inherent in the political engagement and discourse of individual citizens. Hence, the study examined Twitter discourse on the 2019 pre-presidential election campaign in Nigeria. Purposive sampling technique with thematic textual research method was used to thematically analyse tweets based on the research questions. Findings from the study showed that the kind of engagement made or done by Nigerians regarding the 2019 pre-presidential election campaigns was based on the topic, with most topics being met with sarcasm. The sarcasm found in the tweets pointed to the way Nigerians react in a situation that they have no way of rectifying. Also, findings from the study showed that celebrity tweet gets more engagement compared to tweets made by unpopular tweeps. Conclusively, the study found that the level of discourse on Twitter regarding Nigeria s 2019 pre-presidential elections was very rich and participatory this implies that Nigerians have a high propensity to relate on social media as their rate of responses as well as their frequency of responses remained high throughout the election campaign period which to a large extent predicts real-life events.